Upaya Meningkatkan Kecerdasan Naturalis Anak Usia 3-4 Tahun Melalui Bermain Kreatif Berbasis Area - Susmini, Susmini (Program Studi Pendidikan Guru Raudlatul Athfal, UIN Sunan Kalijaga Yogyakarta, 2018)
This study aims to determine the naturalist intelligence of children aged 3-4 years in Amanah Family Planning Guwo Tlogowungu Pati 2016/2017 academic year. 2) and to determine the increase in naturalist intelligence of children aged 3-4 years in Amanah Guwo KB Tlogowungu Pati 2016/2017 school year through area-based creative play. This research method uses a type of classroom action research. This research was conducted in two stages, namely cycle I and cycle II. The subjects of this study were students of Amanah Play Group aged 3-4 years Guwo Tlogowungu Pati as many as 20 students. The results of this study indicate that area-based creative play to improve children's naturalist intelligence is carried out with two cycles, the first cycle is carried out by opening 4 areas. The second cycle is done by opening 5 game areas. The results of data analysis and observation through area-based creative play showed an increase from the pre-cycle of 35% of children who completed their naturalist intelligence, increasing in the first cycle to 61%. That is, an increase of 30%. In cycle II it increased to 80% and there was an increase of 85%. The results achieved in the second cycle had fulfilled the intended completeness target, namely 80% of all children scored with a complete category of 85. This increase in the average value proved the success of area-based creative play to improve children's naturalist intelligence.